The use of the Istanbul Protocol in Israel: Insights at the reception of the revised (2022) version - Weishut, Daniel; Steiner-Birmanns, Bettina; R. Aitchison, Lucy; Senesh, David; Korman, Alona (Torture Journal, 2023)
Health professionals and lawyers in Israel have used the Istanbul Protocol (IP), the internationally accepted protocol for documenting torture and ill-treatment, for many years (Abu Akar et al., 2014; Weishut, 2022; Weishut et al., 2023). A complete IP report requires substantial effort and investment of - mostly pro bono - experts, while the IP interview on which it is based is often an emotionally burdensome experience for clients. This paper presents insights about the use of the IP in Israel, as collected by a group of experts in the documentation of torture and ill-treatment, at the reception of the revised (2022) version.